Gold Contact Allergy. Issue 2 (March 2015) - Chen, Jennifer K.; Lampel, Heather P.
<x xml:space="preserve">Abstract</x> Abstract In 2001, gold was named Contact Allergen of the Year. More than a decade later, we continue to face several challenges in defining the role of gold in contact allergy. First, interpretation of gold reactions in the setting of epicutaneous patch testing may be difficult; in addition to being a common irritant, gold may be associated with significantly delayed and persistent reactions. Second, although gold compounds are commonly positive on patch testing, clinical relevance is relatively low and may be challenging to determine. Third, the complex interplay between gold and the human body is still poorly understood. In this review, we provide an overview of the literature concerning gold patch test positivity and present recommendations for epicutaneous patch testing with gold.